Policy as planned? The implementation of welfare-to-work programs in Manitoba and Ontario - Schaan, Mark (Revue Gouvernance / Governance Review, 2005)
New fiscal pressures, rising neo-conservatism, and a general desire to reinterpret social rights and responsibilities have led to the emergence of welfare-to-work policies in Canada and internationally. This paper seeks to understand welfare-to-work and, most importantly, its implementation. The paper begins with a look at the rich literature on the emergence of welfare-to-work, making an important distinction between “insertion” models and “workfare” models. In either format, welfare-to-work indicates a marked shift away from social rights towards an emphasis on personal obligation and responsibility. While the “new welfare” has received considerable attention, the implementation of such policies is a neglected area. This paper argues that studying implementation is crucial to the outcomes of policy reform : policy is, effectively, remade on the ground level. Understanding the importance of street-level bureaucracy, the paper questions whether the shift in welfare is replicated in implementation and how it varies across systems and models. Utilizing qualitative data from two months of non-participant observation and over 40 interviews with welfare-to-work participants and workers in Manitoba and Ontario, the paper argues that the interactions between workers and clients can greatly alter the focus and nature of significant pieces of welfare-to-work policies. The paper argues that discretion at the implementation level, mitigated by time, information and attitude, is crucial in understanding the impact of policy. It concludes by discussing the implications of the findings on the importance of discretion. The implications include positing a role for street-level bureaucrats in devising policy to ensure effective implementation and also questioning to what degree we can understand welfare reform in the past two decades without significant implementation data.